Pengaruh Media Pembelajaran Herbarium Terhadap Minat Belajar Pada Mata Pelajaran IPA Siswa Kelas 3 SDN 94 Palembang - Wati, Ambar (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This research aims to determine the influence of herbarium learning media on learning interest in science subjects for class III students at SDN 94 Palembang. This research uses a quantitative approach, in this research it uses two variables, namely (X); Herbarium Learning Media and (Y): Student Learning Interests. The type of design used by researchers is Quasi Experimental Design with a Nonequivalent Control Design which consists of an experimental class and a control class. The population in this study was 45 students. The sample was determined using a saturated sampling technique (total sampling) in which the entire population was used as a sample. The sample in this research was class III A, 17 students and III B, totaling 28 students. Data collection techniques in this research are questionnaires and documentation. The data obtained was then calculated using SPSS 25 with the criteria that if t_(count) > t_(table) then Ha was accepted and Ho was rejected. Based on the results of the hypothesis test, the t_count value was 2.789 and the t_table value was 1.679, meaning the value of t_(count) > t_(table) then Ha is accepted and Ho is rejected, therefore it can be concluded that there is a significant influence of Herbarium Learning Media on interest in learning in science subjects for class III students. In other words, the use of Herbarium Learning Media is quite effective for use in learning and has a significant impact.